Peran Gaya Pengasuhan Orang Tua dalam meningkatkan Kecerdasan Emosional pada Siswa Madrasah Ibtidaiyah di Kecamatan Pasar Minggu Jakarta Selatan - Rahmasari, Vina; Elmanora, Elmanora; Oktaviani, Maya (Jurnal Gentala Pendidikan Dasar, 2023)
This study aims to determine whether there is a relationship between parenting style and emotional intelligence in elementary school students in Pasar Minggu District, South Jakarta. This research is a quantitative study using a survey method with a correlational approach. Collecting data in this study using a questionnaire directly. Retrieval of data using simple random sampling technique. Sampling was carried out in five schools involving 309 students and parents of Madrasah Ibtidaiyah students in Pasar Minggu district, namely MI Al-Hidayatussalafiyah, MI Sirojul Muslimin, MI Al Hikmah, MI Nurul Hidayah JP, and MI Faturrahman. The data collection for this study starts from January 2022 to July 2022. To analyze the relationship between the test variables used is the Spearman rank correlation. Before being tested, the data was tested for prerequisites, namely the normality test using the Kolmogorov-Smirnov. The results showed that there was a relationship between parenting style and students' emotional intelligence of 0.302 with sig. 0.000. Which means that parenting style is significantly related to students' emotional intelligence. The better the parenting style applied by parents, the better the emotional intelligence of students. Thus, parents are advised to apply positive parenting styles, such as the emotional coach parenting style.